Repair of Acute Patellar Tendon Rupture Using an Internal Brace Technique - Aki Fukuda; Shigeto Nakazora; Akinobu Nishimura; Ko Kato (Case Reports in Orthopedics)
Acute patellar tendon rupture is a serious injury, resulting in the disruption of the knee extensor mechanism. Many authors recommend augmented repairs of patellar tendon ruptures to allow early active rehabilitation. An internal brace technique, which is a ligament augmentation using high-strength suture tape and knotless anchors, has been used as augmentation for the primary tendon or ligament injury. A case of acute patellar tendon rupture in a Judo player, who was successfully treated with primary repair and augmentation using an internal brace technique, is presented. In this case, the patient regained full function of the knee and returned to full sports activities postoperatively. An internal brace technique provides biomechanical stability of the repaired tendon without donor site morbidity and could be an effective procedure for the treatment of acute patellar tendon rupture.